Analisis Strategi Account Officer (AO) Dalam Mencapai Target Pembiayaan Pada Masa Pandemi Covid -19 di Bank Pembiayaan Rakyat (BPR) Syariah Tanmiya Artha Kediri - Moch. Uzeir Mustaqfirin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
The background of this research is that BPR Syariah Tanmiya Artha Kediri is one of the Islamic financial institutions that are currently in the stage of growing and developing well. This is evident from several awards and achievements that have been achieved. And for now, as we know from the Covid-19 pandemic, many Islamic financial institutions have been affected by the Covid-19 pandemic, including BPR Syariah Tanmiya Artha Kediri. One of them has an impact on the account officer (AO). The data collection method uses observation, interview and documentation techniques. To avoid mistakes, an examination of the validity of the data is held with member chek and triangulation techniques. Research results: 1) Sharia People's Financing Bank (BPRS) for the first time in Kediri on April 24, 2008, which was initiated by KH. Anwar Iskandar with the reason for having a BPR with Islamic nuances and the BPRS that has been formed is named the Sharia People's Financing Bank (BPRS) Tanmiya Artha. 2) Tanmiya Artha Sharia BPR Products Including Funding Products (IB Mudharabah Savings, Wadiah Savings, Hajj Savings, Sacrificial Savings, IB Mudharabah Deposits). For Financing Products, there are types of financing: Working capital, Investment, Consumptive, and Multipurpose financing. And for Services there is Wakalah. 3) Among the strategies carried out with a personal and cultivation approach. And coupled with some pretty important techniques that are: Effective listening and speaking skills. 4) The analysis obtained is as follows: Strenght (strategic location, few competitors, and quite varied products). Weakness (weak public understanding of BPRS). Opportunity (the number of Muslim citizens of Kediri is dominant). Treatment (the emergence of new Islamic financial institutions).